Impact of protein oxidation induced by different cooking methods in channel fish (Ietalurus punetaus) on structure and in vitro digestion of protein. (9th July 2022) - Jiang, Qixing; Zhang, Zhiyun; Yang, Fang; Gao, Pei; Yu, Dawei; Xu, Yanshun; Xia, Wenshui
Summary: This study was designed to evaluate the effect of different cooking methods on the protein digestion characteristics of channel fish ( Ietalurus punetaus ). The channel fish muscles were subjected to different cooking methods, namely boiling, steaming and roasting and were subjected to in vitro gastrointestinal digestion simulation using raw fish as a control. All the cooking methods increased the protein digestibility (1.60–8.28%) and decreased the protein particle size at the end of the gastrointestinal digestion. The highest protein digestibility (66.78%) and the smallest protein particle size values (600.7 nm) were observed for the steamed group. Samples which were steam cooked showed lowest β ‐sheet content (9.63 ± 0.81%) and were accompanied with moderate protein oxidation. As the core temperature increased from 40°C to 90°C, protein oxidation increased significantly ( P < 0.05) with the increase of carbonyl groups and Schiff bases and decrease of sulfhydryl groups in all cooked groups. Based on the results, steaming was recommended as the best methods of cooking channel fish for improved protein digestibility.